Analisis Pengaruh Kualitas Pelayanan, Harga, Fasilitas Dan Customer Loyalty Terhadap Kepuasan Pasien Rawat Jalan Pada Rumah Sakit Medika Permata Hijau Jakarta - Sri Mulyono (UIN Raden Mas Said Surakarta, 2019)
Medika Permata Hijau (RSMPH) Hospital is one of hospitals affiliated in KPJ Health Care (Bhd) managing 25 hospitals centered in Kuala Lumpur, Malaysia and two hospitals in Indonesia. This study has some objectives which are to analyze the service quality influence towards outpatients’ satisfaction, the cost influence towards outpatients’ satisfaction, the facility influence toward outpatients’ satisfaction, customer loyalty influence towards outpatients’ satisfaction. This study uses quantitative method with research object discussed in this study I outpatients of Medika Permata Hijau Jakarta Hospital. The participants of this study were conveniently selected by employing non probability sampling technique. The validity of the data were analyzed by using Pearson Correlation Test, and the reliabitity of the data were analyzed by using Cronbach’s Alpha score in X1, X2, X3, X4, X5, and Y variable have value score more than 0,6 in each variable. Therefore, the question item of variable are reliable. The results of this study are service quality gives significant influence on outpatients’ satisfaction, cost does not give significant influence on outpatients’ satisfaction, facility does not give significant influence on outpatients’ satisfaction, and customer loyalty gives significant influence on outpatients’satisfaction. The result of this study have contribution in improving the hospital’s service quality.